Mealtime food art - Peterson, Tamara J. M., 1972- (North Mankato, Minn. : Capstone Press, 2025)
"Tired of boring meals? Unleash your inner food artist! Transform everyday ingredients into meals that look beautiful and taste even better. Arrange sliced fruit to create memorable morning toast. Cook up a spaghetti nest with meatball birds. Make hotdog racecars for a racetrack platter. What food art will you create?"--Provided by the publisher.
Transforming ingredients into food art! -- Kitchen tips -- Oatmeal mandala -- Breakfast feast -- Morning toast -- Bagel charcuterie board -- Caprese caterpillars -- A swimming sandwich -- Itty-bitty sandwich buddies -- Noodle heads -- Hot dog race cars -- Spaghetti birds' nests -- Flower potpies -- Pizza art -- Football burgers.
Includes bibliographical references (p. 32).
4-8
760
3-4.
3-5.
Keywords: Cooking